2003
DOI: 10.2337/diacare.26.12.3243
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal Advantages in Postprandial Lipid Metabolism Are Lost in Women With Type 2 Diabetes

Abstract: OBJECTIVE -Women with type 2 diabetes appear to lose the protection against cardiovascular disease afforded by estrogens. We examined the effects of menopausal status on postprandial clearance of dietary fat in healthy and diabetic women.RESEARCH DESIGN AND METHODS -Fasting subjects (premenopausal and postmenopausal control subjects, premenopausal and postmenopausal diabetic women, all n ϭ 8) were given a meal containing the stable isotope 1,1,1-13 C-tripalmitin, with blood and breath sampled for 6 and 24 h, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
4
19
1
1
Order By: Relevance
“…In fact, while non-diabetic women are relatively protected from cardiovascular disease, this advantage is lost in diabetes [6]. In the Framingham study, the reported incidence of symptomatic HF was 2.4-fold higher in men and 5.0-fold higher in women with diabetes compared to their non-diabetic peers, [7] a finding confirmed by several other studies [8-10].…”
Section: Introductionmentioning
confidence: 69%
“…In fact, while non-diabetic women are relatively protected from cardiovascular disease, this advantage is lost in diabetes [6]. In the Framingham study, the reported incidence of symptomatic HF was 2.4-fold higher in men and 5.0-fold higher in women with diabetes compared to their non-diabetic peers, [7] a finding confirmed by several other studies [8-10].…”
Section: Introductionmentioning
confidence: 69%
“…People with type 2 diabetes mellitus were recruited from a hospital clinic (controlled by diet or oral hypoglycemics), whereas controls were recruited from the community via advertising. All women were postmenopausal (some of these volunteers were a subgroup of the postmenopausal female volunteers described by Masding et al [19]). Postmenopausal status was verified by amenorrhea for more than 1 year and elevated gonadotrophins.…”
Section: Methodsmentioning
confidence: 99%
“…Serum triglycerides, insulin, and glucose were measured using standardized laboratory techniques as described in reference [19]. Plasma sialic acid was quantified using an enzymatic method (Boehringer Mannheim, Lewes, Sussex, UK) on a Roche Cobas Fara analyzer (Roche, Basel, Switzerland) [20].…”
Section: Methodsmentioning
confidence: 99%
“…Studies assessing dietary fatty acid oxidation using 13 C-labeled fatty acids have shown that meal fatty acid oxidation tends to increase with body fat mass [89], in abdominally obese versus control men [90] and is increased in postmenopausal women with T2D [91]. It should be noted that rates of dietary fatty acid oxidation were likely underestimated in the latter studies because correction for the acetate retention factor was not applied.…”
Section: Abnormal Lean Tissue Fatty Acid Metabolismmentioning
confidence: 99%